Key aspects of political relations between the Republic of Kazakhstan and the People's Republic of China (Journal of Philosophy Culture and Political Science, 2018)
In given article it is analyzed the basic aspects of political mutual relation between Republic Kazakhstan and the Chinese National Republic.